EVALUASI PERAN DAN TANTANGAN KANTOR DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DI NUSA TENGGARA TIMUR - Antonius Toni Fernandez; Bruno Rey Sonby Pantola (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
This study aims to assess the contribution and identify the various challenges faced by the Regional Office of the Regional Representative Council of the Republic of Indonesia (DPD RI) in East Nusa Tenggara Province as a supporting system for the implementation of the constitutional duties of DPD RI members. The method used in this study is a qualitative approach with a descriptive research type. Data were collected through in-depth interviews, observations, and document analysis, which were then analyzed through data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the role of the DPD RI Office in East Nusa Tenggara Province has not been functioning optimally. This is reflected in weak administrative support due to limited facilities and infrastructure, as well as dependence on central government policies. In addition, cooperation between the secretariat and DPD RI members has not been maximized due to the low frequency of communication and member visits to the region. The function as an activity facilitator has also not been carried out consistently because it is highly dependent on the presence of DPD RI members. On the other hand, the effectiveness of the institution’s performance is still far from expectations due to limited funding, lack of authority, and the strong influence of central government policies. The conclusion of this study shows that there is a need for more decentralized organizational reforms, increased resource support, and strengthened coordination and institutional capacity so that regional DPD RI offices can optimize their functions in representing local interests